Virtual Server - Gozali, Ferrianto; Alex, Alex (Jurnal Teknik Elektro, 2002)
The rapid development of Internet technology can be reflected by the increasing number ofthe Internet users, the complexity of the applications in the Internet and its related computernetwork technology. Nowadays, more and more companies are moving their businesses onthe Internet. Once the companies have decided that they want to utilize the internet tosupport their business activities, their consideration not only based on their needs when thesystem is set up but also the prediction about future condition. Any interrupt or stop ofservices on the servers means business losses, and high availability of these servers becomesincreasingly important. The load on popular Internet sites is growing rapidly, some havealready got tens of millions hits per day. More and more administrators have met theperformance bottleneck problem of their servers, and with the increasing access requests theservers will be easily overloaded for a short time. This condition sometimes exceeds theirprediction when they first set up the system. This paper presents how to create Linux virtualservers or in brief we called LVS. LVS implements parallel processing concepts in the Linuxbased computer network. LVS is a high-performance and highly available server built on acluster of real servers. By utilizing one computer as a LVS Director which is responsible todistribute user accesses, LVS will be able to schedule and distribute the load into number ofLVS real server. In the system, we utilize the method of IP-level load balancing to makeparallel services of the cluster to appear as a virtual service on a single IP address viaNetwork Address Translation. They are two scheduling algorithms used, a Round Robin andWeight Least Cost load balancing. In order to test the performance of the LVS system, anLVS Web server is developed in the Computer System Laboratory, Electrical EngineeringDepartment, Trisakti University. The response of the web server using different number ofreal servers and different load balancing algorithm, round robin and weight least cost, ismonitored.Keywords: Internet, LVS, NAT, komputer Cluster, Round Robin, Weight Least Cost.